Investigation of factors determining the critical wall thickness in electrical discharge machining - Radhakrishnan, Jayakrishnan (2012)
The project aims to investigate the factors determining the critical wall thickness in electrical discharge machining and there by arrive at an equation that can deduce the optimal wall thickness. This was facilitated by the measurement and analysis of the critical wall thickness of four different materials using SEM (JSM-5600 LV). 1100 Aluminium, Galvanized Steel,304 Stainless Steel and Syalon 501 were chosen for the analysis due to their wide spread usage in the industry. Experimental results proved that the critical wall thickness of materials have been increased by an increase in the discharge energy for these materials. Based on the properties, the critical wall thickness has been varied for different materials. As a result, the equations have been derived for these materials. The hardness of the machined work piece has been studied by using a micro hardness tester. It is observed that the hardness of the work piece decreases with a decrease in the discharge energy.